Assessing the investment risk: An empirical analysis of Altman’s Z-score model - Kazi Afaq Ahmed; Ambreen Fatima; Fouzia Sohail; Khalid Jamal (PLoS ONE, 2026)
Investors can play a significant role in reviving the economy and addressing the national agenda of poverty elimination through job creation. Though foreign and local investment are the backbone of any economy, especially in developing economies like Pakistan, investors face the challenge of assessing investment risk to protect the capital employed and achieve an appropriate return on investment. The aim of this research is to assess investment risk faced by firms in Pakistan using the most suitable approach, and then to develop an economic model for a comprehensive assessment of the factors influencing investors’ risk, focusing on firm-specific characteristics, economic conditions, and political stability. The introduction of the Investment Risk Index based on Altman Z-scores provides a structured diagnostic approach to assessing investment risk in Pakistan. Earlier studies have mainly used financial ratios to explain risk. The estimation results using an analytical approach (the Investment Risk Framework) confirm that firm-specific characteristics and economic, political, and financial stability indicators significantly impact investment risk. The findings, based on 443 firms over the period 2014–2023, reveal that the proportion of firms in the distress zone increased from 4.8% to 8.5% (a doubling) during the study period. Retained earnings relative to total assets emerged as a strongly correlated factor with investment risk, while the market value of equity relative to total liabilities played a significant role in keeping firms (around 88% of the sample) in the safe zone. For the determinants, the GMM results indicate that past values of investment risk strongly predict future risk. A 1% increase in past risk is associated with a 0.395% higher future risk. Additionally, political stability, GDP growth, inflation, current account balance, broad money, dividend premium paid, and growth opportunities are found to have a significant impact on the investment risk. Furthermore, internal factors such as fixed asset accumulation, firm size, and tax expenses also influence risk, with larger firms facing higher risk. This study underscores the importance of understanding investment risk factors for informed decision-making. The findings offer valuable insights for investors and policymakers, with potential applicability to other developing economies.